Lessons from 11 years of CCAFS low-emissions development research - Wollenberg, Eva Karoline (2022)
Lessons from 11 years of CCAFS Low-Emissions Development Research was presented by Lini Wollenberg at a USAID Research Webinar on June 27, 2022. Additional resources, include the CCAFS AgLED website, the Agrochain Emissions Calculator (ACE), Our World in Data, and FAO emission intensity and food systems data.